2004
DOI: 10.2134/jeq2004.4490
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emissions from Swine Houses in the Southeastern United States

Abstract: Ammonia (NH3) from confined animal feeding operations is emitted from several sources including lagoons, field applications, and houses. This paper presents studies that were conducted to evaluate NH3 emissions from swine finisher and sow animal houses in the southeastern USA. Management and climate variables including animal weight, feed consumption, housing gutter water temperature, total time fans operated per day, house air temperature, house ambient NH3 concentration, and animal numbers were measured to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
1
18
0
3
Order By: Relevance
“…The emission factors used in this study were adopted because they were determined to be the most applicable to the defined conditions of the processes in the systems analyzed, such as the climate, animals, and styles of housing and waste treatment. For example, the emission factor suggested by Harper et al (2004) was used to calculate NH 3 emission from the pig barn considering the conditions of housing such as the slat floor and the daily removal of manure, rather than the storage of manure in an under-floor pit for a long period. To calculate the environmental loads from the production and combustion of fossil fuels, the consumption of electricity, the production of materials, and marine transport, the database of the LCA software JEMAI-LCA Pro (JEMAI 2005) was used, and if the data for materials were lacking in the database, inputoutput-based databases were used (NIES 2002;Ajinomoto 2007).…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…The emission factors used in this study were adopted because they were determined to be the most applicable to the defined conditions of the processes in the systems analyzed, such as the climate, animals, and styles of housing and waste treatment. For example, the emission factor suggested by Harper et al (2004) was used to calculate NH 3 emission from the pig barn considering the conditions of housing such as the slat floor and the daily removal of manure, rather than the storage of manure in an under-floor pit for a long period. To calculate the environmental loads from the production and combustion of fossil fuels, the consumption of electricity, the production of materials, and marine transport, the database of the LCA software JEMAI-LCA Pro (JEMAI 2005) was used, and if the data for materials were lacking in the database, inputoutput-based databases were used (NIES 2002;Ajinomoto 2007).…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…On slatted floor, cited values range from 5 g to 15 g NH 3 -N/day per sow (Groot Koerkamp et al, 1998;Groenestein et al, 2003). Whatever the floor type, numerous factors can influence NH 3 -emissions, like feeding management, interior climate, season and waste treatment (Harper et al, 2004;Philippe et al, 2006 and. Furthermore, for litter systems, properties of bedding materials carbon/nitrogen ratio (C/N ratio; carbon availability, pH value and physical structure, among others) affect volatilization (Jeppsson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…No N 2 O was found in the collectors via GC. In other studies no N 2 O emissions were found from anaerobic lagoons using atmospheric transport techniques and tunable diode laser spectroscopy (Harper et al 2000(Harper et al , 2004a. Samples of helium (He) injected into the collectors showed a sampling procedure error of about 1 % due to atmospheric N 2 contamination (see Harper et al 2004b).…”
Section: Methodsmentioning
confidence: 97%
“…measurements of effluent samples (collected in bottles at the surface of each lagoon), surface lagoon temperatures, and wind speeds measured at 1.5 m height (from a metereological station on site), and a lagoon NH 3 emissions model by De Visscher et al (2002). Housing NH 3 emissions were estimated from a model developed by Harper et al (2004a) for North Carolina swine farms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation